Educational Ideas in Makhtumkuli’s Work (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, some poems of Makhtumkuli Firoghi were analyzed. Also, attention was paid to the issues of artistic features and poetic skill in the poet's poems.